Chilled foods : a comprehensive guide - Stringer, Michael, 1950-; Dennis, C. (CRC Press ; Woodhead Pub., 2000)
Examines aspects of the chilled food industry including the market, applicable legislation, variety selection, refrigeration, temperature control, quality and safety, microbiology, and shelf-life.
Keywords: Frozen foods.; Cold storage.; elektronické knihy; electronic books